Restructuring of Regency/City General Election Commission Organizations In West Java - Abdal Abdal; Benyamin Harits; Ikin Sodikin (Doctoral Program of Social Science Pasundan University, 2020)
Research on the General Election Commission as the organizer of general elections has been done a lot. However, the research that examines the organizational restructuring of the Regency / City General Election Commission in West Java, in particular, no one has done yet. This study explores the existence and organizational restructuring of the Regency / City General Election Commission in West Java as the organizer of the General Election. This study uses a qualitative method with descriptive analysis with a case study strategy of organizational restructuring of the Regency / City General Election Commission in West Java. Qualitative methods produce descriptive data in the form of words from the object under study and understand the phenomena experienced by research subjects—the technique of collecting data using observation, interviews, documentation, and forum group discussion (FGD). Data analysis was performed through data reduction, display data, and conclusion drawing/verification procedures. The research results obtained, firstly, the existence of the Regency / City General Election Commission is still needed as the organizer of general elections at the regional level, but is ad hock in nature. Second, restructuring the organization of the Regency / City Election Commission, which includes: Downsizingor organizational downsizing. Delayering or grouping the types of work. Decentralizing or handing over some functions and responsibilities to lower levels of the organization. Reorganization or review or restructuring (refocusing) on the organization's core competencies (core competition). Cost reduction strategy or use of resources. IT Innovation or adjustment of work with technological developments. Competency measurement or measuring the competencies needed by employees. Performance-related pay or an assessment of performance. The restructuring model from Bernadin and Russel (1998: 210) in their realization has not been effective and has not been optimally implemented at the Regency / City General Election Commission in West Java.